OPTIMIZIMG OF MANAGEMENT OF THE OVARIAN CANCER PATIENTS WITH PERITONEAL CARCINOMATOSIS - Рибін, Андрій; Кузнецова, Ольга; Пацков, Андрій (SWorldJournal, 2024)
Objective: At present, common forms of cancer of different localization can not be ignored. New approaches to the treatment of metastatic lesions have some success in clinical application. This study is devoted to the experience of using the technology of